(untitled) (Journal of Economic Research & Business Administration, 2017)
The aspects of corporate culture – the most important element of prosperity of the entities, shown in a value system, in the principles of structural and personnel policy, traditions of the organization, the interpersonal relations and in special internal environment of corporation are considered in this article. Functions of corporate culture are determined, as well as a number of components of corporate culture which shall be accepted and be supported by all members of the collective is shown. Positive and negative corporate cultures are allocated, their role in increase of overall performance or preventing to normal functioning of the organization and accomplishment of its mission are shown. The main forms of existence of corporate values are considered: the ideals developed by a management; the embodiment of these ideals within the organization; internal motivational structures of the identity of staff of the organization. The increase of the level of corporate culture, forming of reasonable valuable orientations, isettings, regulations, the relations are the important conditions of effective functioning of the organization.